Accuracy Comparison between GPS Real Time Kinematic (RTK) Method and Total Station to Determine The Coordinate of An Area - Safrel, Ispen; Julianto, Eko Nugroho; Usman, Nur Qudus (Semarang State University, 2018)
Abstract. Survey with GPS Real Time Kinematic (RTK) has the advantage of being faster and easier than the total station, but on the other hand the accuracy of GPS Real Time Kinematic (RTK) is considered lacking. This study was to determine the comparison of accuracy and efficiency of measuring land parcels using a total station and GPS Real Time Kinematic (RTK) method. The research location is at the Universitas Negeri Semarang campus by selecting areas that are open or unobstructed to satellites and congested areas or which have many obstacles to satellites. The results of this study indicate that for open areas, measurement with GPS Real Time Kinematic (RTK) method reaches a horizontal accuracy of 0.040 m with a time of 16 minutes 16 seconds. While the measurement using a horizontal accuracy of 0.00 Total Station with a length of time of 26 minutes 47 seconds. For areas that are densely measured, GPS Real Time Kinematic (RTK) achieves horizontal accuracy of 10.053 m with a length of time of 39 minutes 27 seconds. While the measurement using a precision horizontal Total Station 0.00 with the length of time 25 minutes 41 seconds.